DEFINING A SAFE ZONE FOR ALL INSIDE LATERAL MENISCUS REPAIRS IN PEDIATRIC PATIENTS: A MAGNETIC RESONANCE IMAGING STUDY. Issue 3 (31st March 2019) - Beck, Jennifer; Shifflett, Kendall; Greg, Danielle; Ebramzadeh, Edward; Bowen, Richard E.
Purpose: All-inside posterior horn lateral meniscal (PHLM) repair puts the popliteal neurovascular bundle (PVNB) at risk of injury by meniscal repair devices. The purpose of this study was to establish a safe zone of all-inside meniscal fixation in pediatric patients using MRI measurements between the popliteus tendon (PT) and popliteal neurovascular bundle (PNVB). We hypothesize that males and older age groups will have a larger distance between PT and PNVB. Methods: Axial MRIs of 250 pediatric (5-16 yrs.) patients were retrospectively reviewed. Patients were grouped by age: group I (5-7yrs.): 61; II (8-10yrs.): 59; III (11-13yrs.): 60; IV (14-16yrs.): 70. At the level of the lateral meniscus, two lines starting at the lateral patella tendon border ending at the medial edge of the PT (D1) and the lateral edge of the PNVB (D2) were made on an axial knee MRI. D3 connected D1 to D2 at the meniscocapsular junction of the PHLM. D4 was derived geometrically, parallel and 8 mm anterior to D3 simulating the anterior edge of the PHLM. Results: Analysis showed significant correlation between age and sex for D3 (p<0.0001). For D3, there were significant differences among all age groups, except between groups III and IV. Average (STD) D3 for age groups was: 14.1mm(3.1), 15.8(2.5), 17.0(3.3), 17.2(3.1). For D4, the average (STD) was: 11.9 mm(2.9); 13.9(2.5); 15.4(3.0); 15.2(2.9). There was significant difference in D3 and D4 in males versus females (17.6 vs 15.7 mm; p <0.001; 14.9 vs 13.2; p <0.001), particularly in III and IV (17.0 vs 13.8 and 16.8 vs 13.9). Conclusions: This study provides normative data of the distance between popliteal neurovascular bundle and popliteus tendon at the meniscocapsular junction (D3) and anterior edge of the posterior horn lateral meniscus (D4) with the knee in full extension. Combined with previous studies showing the addition of knee flexion increases the distance between the meniscus and the neurovascular bundle, surgeons can use this data to improve safety of posterior horn lateral meniscus repair in pediatric patients.